Implementation of an IoT-based Automatic Watering System in Highland Community Agricultural Land - Okta Andrica Putra; Hadi Syahputra; Hasri Awal (Majalah Ilmiah UPI YPTK, 2026)
Farming in highland areas faces unique challenges such as changes in temperature, high humidity, and limited access to technology information. This community service activity aims to boost farming productivity by using the Internet of Things (IoT) for monitoring and managing agricultural land. The methods used include identifying the problems faced by farmers, designing an IoT system based on environmental sensors, and providing support and training on how to use the technology to the community. The IoT system that has been set up can monitor the temperature, air humidity, and soil moisture in real-time. This helps farmers make decisions about irrigation and taking care of their plants. The results of the activity show that there has been an improvement in how efficiently water is used, a decrease in the risk of crop failure, and an increase in agricultural production. In addition, support and technical training improve farmers' skills in using the system, making the adoption of technology more effective. Therefore, using IoT in highland farming can be a smart way to boost efficiency, productivity, and sustainability in agriculture in highland areas.